Active tectonics of eastern segment of the South Wagad Fault Zone, Kachchh, Western India. (20th October 2021) - Lakhote, Abhishek; Thakkar, M.G.; Kandregula, Raj Sunil; Kothyari, Girish Ch; Chauhan, Gaurav
Abstract: The present study describes the active tectonic features of the eastern segment of the South Wagad Fault Zone (SWFZ) of the Kachchh Rift Basin (KRB). The SWFZ defines the southern margin of the Wagad uplift with a series of small domes and anticlines forming a low hill range. Geomorphologically, the SWFZ is expressed by the presence of the South Wagad Hill range to the north and the south sloping Samkhiyali and Lakadia plains to the south. The easternmost part of the SWFZ consists of domes and anticlines having a rugged topography, which comprises of Mesozoic to Neogene rocks and is practically unexplored as far as their active tectonic characterizations are concerned. The geomorphic expression of the SWFZ in the eastern segment consists of the Gagodar, Kanmer, Guan and Mardak domes and anticlines. They are exposed as a series of linear mounts projected amidst the Little Rann of Kachchh and surrounded by the alluvial sediments of easterly flowing rivers as well as the Rann sediments. The active nature of the eastern SWFZ is portrayed by warping, flexuring, alluvial fans, tilted Quaternary deposits, scarps, gullied surfaces, slickensides and knickpoints. Presence of wave cut cliff and notches at Mardak Bet suggests that the eastern segment of SWFZ is marginally uplifted during Middle to Late Holocene period. We provided a detailed morphotectonic map of the eastern segment of SWFZ, which can be used for future infrastructural development, town planning and seismic hazard assessment in the region. Further, the study suggests that the seismically silent eastern segment of the active SWFZ is capable of generating a large magnitude earthquake similar to the 2001 Bhuj earthquake or the 1819 Allah Bund earthquake in the future, owing to long-term stress accumulation.